Deadly Vegas escapade - Stewart, Anna J. (Stewart, Anna J. Honor bound., 2023)
"On the lam from a murder charge, Riordan Malloy is saved from drowning by water rescuer Darcy Ford. On land, the mysterious man has no memory of his identity or his secret past. He only knows that he's endangering Darcy. When all clues lead the unlikely pair to a posh Vegas casino, they must fight to stay alive--and fall in love--against all odds." -- Page [4] cover.